All Hands on Deck: Transdisciplinary Approaches to Emerging Infectious Disease - Breilh Paz y Miño, Jaime Eduardo (2005)
The increasing burden of emerging infectious diseases worldwide confronts us with numerous challenges, including the imperative to design research and responses that are commensurate to understanding the complex social and ecological contexts in which infectious diseases occur. A diverse group of scientists met in Hawaii in March 2005 to discuss the linked social and ecological contexts in which infectious diseases emerge. A subset of the meeting was a group that focused on ‘‘transdisciplinary approaches’’ to integrating knowledge across and beyond academic disciplines in order to improve prevention and control of emerging infections. This article is based on the discussions of that group. Here, we outline the epidemiological legacy that has dominated infectious disease research and control up until now, and introduce the role of new, transdisciplinary and systems-based approaches to emerging infectious diseases.Wedescribe four cases of transboundary health issues and use them to discuss the potential benefits, as well as the inherent difficulties, in understanding the social–ecological contexts in which infectious diseases occur and of using transdisciplinary approaches to deal with them.